2002
DOI: 10.1074/jbc.m109165200
|View full text |Cite
|
Sign up to set email alerts
|

SH2-B Family Members Differentially Regulate JAK Family Tyrosine Kinases

Abstract: Activation of JAK tyrosine kinases is an essential step in cell signaling by multiple hormones, cytokines, and growth factors, including growth hormone (GH) and interferon-␥. Previously, we identified SH2-B␤ as a potent activator of JAK2 (Rui, L., and Carter-Su, C. (1999) Proc. Natl. Acad. Sci. U. S. A. 96, 7172-7177). Here, we investigated whether the activation of JAK2 by SH2-B␤ is specific to JAK2 and SH2-B␤ or extends to other JAKs or other members of the SH2-B␤ family. When SH2-B␤ was overexpressed with J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 67 publications
1
46
1
Order By: Relevance
“…A differential tyrosine phosphorylation status can give rise to different IC 50 values as exemplified for the non-versus monoor diphosphorylated forms of the TYK2 kinase domain (29). Third, differential negative or positive feedback mechanisms for JAK1-versus JAK2-dependent signaling by means of phosphatases, members of the SOCS or SH2B families, can have a different impact on the amplitude and kinetics of JAK enzyme activity and signaling output (30)(31)(32)(33). Finally, different small molecules might induce subtle changes in the three-dimensional space of the ATPbinding pockets of the JAKs, leading to differential kinase activity and/or protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A differential tyrosine phosphorylation status can give rise to different IC 50 values as exemplified for the non-versus monoor diphosphorylated forms of the TYK2 kinase domain (29). Third, differential negative or positive feedback mechanisms for JAK1-versus JAK2-dependent signaling by means of phosphatases, members of the SOCS or SH2B families, can have a different impact on the amplitude and kinetics of JAK enzyme activity and signaling output (30)(31)(32)(33). Finally, different small molecules might induce subtle changes in the three-dimensional space of the ATPbinding pockets of the JAKs, leading to differential kinase activity and/or protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Sh2b1 mediates activation of various kinases and may function in cytokine and growth factor receptor signaling and cellular. A recent study found that SH2-B b specifically activates JAK2 and functions as an adapter protein that cross-links actin filaments, leading to modulation of cellular responses in response to JAK2 activation (41,42). Another study shows an essential role of SH2-B b in the activation of the Src kinase and the resulting mitogenic response, causing phenotypic cell transformation involving the Src substrate STAT3 (43).…”
Section: Mouse Models Mouse Modelsmentioning
confidence: 99%
“…SH2B2 binds via both its SH2 domain and non-SH2 domain regions to JAK2, and its SH2 domain binds to phospho-Tyr 813 of JAK2 [16,146] . Unlike SH2B1, SH2B2 is unable to activate, or only slightly activates, JAK2 [61,146] . Multiple cytokines, including interferon-γ, EPO, leukemia inhibitor factor, granulocyte-macrophage colony stimulating factor, interleukin-5 (IL-5) and IL-3, stimulate tyrosine phosphorylation of SH2B2, presumably through JAK family members [135,145,147] .…”
Section: Sh2b2 Structurementioning
confidence: 99%
“…SH2B2 regulates cytokine signaling and immune response Like SH2B1, SH2B2 binds via its SH2 domain to JAK1, JAK2 and JAK3, and is tyrosyl phosphorylated by these kinases [61,145] . SH2B2 binds via both its SH2 domain and non-SH2 domain regions to JAK2, and its SH2 domain binds to phospho-Tyr 813 of JAK2 [16,146] .…”
Section: Sh2b2 Structurementioning
confidence: 99%
See 1 more Smart Citation